Pengaruh kerjasama tim, komunikasi, dan disiplin kerja terhadap kinerja karyawan bagian packing Malkist Keju di PT. Mayora Indah Tbk Jayanti 1 – Tangerang - Jaka Slameta; Peka Yustika Sukma; Rika Nurhidayah (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
This research was conducted in order to gain an understanding of the influence of teamwork, communication and work discipline on the performance of employees of PT. Mayora Indah Tbk. This research uses quantitative methodsThe results of this study are that in the T test the Teamwork variable (X1) has a tcount value of 3.644 and a ttable value of 1.979 this value indicates that the tcount value is greater than the ttable so that Ho is rejected, and Ha is accePTed. In the T test, the Communication variable (X2) has a tcount value of 5.730 and a ttable value of 1.979, this value indicates that the tcount value is greater than the ttable so that Ho is rejected, and Ha is accePTed. In the T test, the Discipline variable (X3) has a tcount value of 7.617 and a ttable value of 1.979, this value indicates that the tcount value is greater than the ttable so that Ho is rejected, and Ha is accePTed. The Fcount value of 355.130 is greater than the Ftable value of 3.07 with a probability value of 0.000 because the probability value is less than 0.05, the regression model can be used to explain the effect of Teamwork (X1), Communication (X2), Discipline (X3) has a joint (simultaneous) effect on Employee Performance (Y). and the value of the adjusted R square is 0.895 or 89.5%. This shows that the variation in variable changes in Teamwork (X1), Communication (X2), Discipline (X3) and Employee Performance (Y) has a percentage value of 89.5%., while the remaining 11.5% is explained by other variables not used in this studyit can be conculeded based on research, teamwork, comuunication and work dicpline on employee performance have a positiveand significant relationship.